Corporate Brand Management in - Siso, Linda (My University, 2011)
Global trends have shown a shift in marketing emphasis from product branding to corporate branding. Some of the reasons cited by prior research for this shift were: high consumer expectations; anti-branding movements that demand a visible link between product brands with companies that produce them; high rising costs in advertising; commoditisation of products; and highly competitive and unstable markets. There is limited practical evidence in the corporate branding field. As such the purpose of the research was to identify the critical success factors of corporate branding in the South African context. In addition the degree to which South African companies have adopted a strategic and crossfunctional approach to corporate branding was investigated. A structured questionnaire was designed and analysed using quantitative research methodology. 100 respondents from 4 industries completed the questionnaire. The research findings identified 3 critical success factors of corporate branding. They were the important role that employees play; top managements’ role and cross functional team alignment; and customer involvement and interaction. In addition the research found that the surveyed South African companies were still far from adopting a strategic and cross-functional approach of corporate branding. Only 3 out of a possible 10 principles were identified as being in place towards the adoption of a strategic and cross-functional approach to corporate branding. The 3 principles identified were: respondents agreed that they were aware of their organisations’ identity; that their organisation’s vision was realistic and that their organisations used contact points with stakeholders to build relationships. In addition the respondents felt that their organisations were not giving adequate attention to corporate branding; providing adequate resources to implement a corporate brand strategy, and there was not enough understanding of the paradoxes of their brands
MBA - WBS
Keywords: Brand management; Brands and branding